The effect of attire attractiveness on students’ perception of their teachers - Marici, Marius; Runcan, Remus; Iosim, Iasmina; Haisan, Alexandra (Frontiers in Psychology, 2023)
Generally, people do judge a book by its cover. The purpose of this research is to investigate the effect of teachers' attire on students' perception of 34 psychological dimensions. The research is an experiment, with self-reported data, in groups, based on a questionnaire. The participants were 173 students (Mage = 12.16, SD = 1.74) from Suceava, Romania. The results indicated that when the teacher is perceived as being more attractive, the students have a greater openness for school activities, the evaluation of the teacher's personality is more positive, the evaluation of the teaching effort is more positive, students expect a higher grade, and the perceived age of the teacher is lower. The article underlines the role of clothing in molding student’s perception and raises questions about dress codes in schools.